A Radar-Enabled Collaborative Sensor Network Integrating COTS Technology For Surveillance And Tracking - Demirer, Rüştü Murat; Kozma, Robert; Wang, Lan; Iftekharuddin, Khan; McCracken, Ernest; Khan, Muhammad; Islam, Khandakar; Bhurtel, Sushil R. (Mdpi Ag, Postfach, Ch-4005 Basel, Switzerland, 2012)
The feasibility of using Commercial Off-The-Shelf (COTS) sensor nodes is studied in a distributed network, aiming at dynamic surveillance and tracking of ground targets. Data acquisition by low-cost (<$50 US) miniature low-power radar through a wireless mote is described. We demonstrate the detection, ranging and velocity estimation, classification and tracking capabilities of the mini-radar, and compare results to simulations and manual measurements. Furthermore, we supplement the radar output with other sensor modalities, such as acoustic and vibration sensors. This method provides innovative solutions for detecting, identifying, and tracking vehicles and dismounts over a wide area in noisy conditions. This study presents a step towards distributed intelligent decision support and demonstrates effectiveness of small cheap sensors, which can complement advanced technologies in certain real-life scenarios.
Keywords: doppler radar; wireless sensor mote; autonomous sensor network; surveillance; tracking; doppler radarı; kablosuz algılayıcı mote; özerk sensör ağı; gözetim; izlemek